Fracture Characteristics of Polyurethane Grouting Materials Based on Acoustic Emission Monitoring - Baihui Ren; Jianjun Shen; Weitao Liu; Yingying Hu; Qing Cao (Shock and Vibration)
In this study, 16 groups of tests were designed by the orthogonal test method, and a PU grouting material was prepared, which can be used for the construction of sealing wall in mined-out area of coal mine. The basic properties of the material were measured. Firstly, the viscosity of four groups of samples with different polyether polyol contents was measured by a dynamic rheometer. Secondly, the uniaxial compressive strength of pure slurry samples and sand-containing samples was measured by a universal testing machine. Finally, the failure process of sand-containing samples was monitored by acoustic emission equipment. Through the above research and analysis, a PU grouting material with excellent performance has been obtained. That is, when the ratio of polyether triol:polyether tetraol:catalyst:surfactant:chain extender:plasticizer is 11 : 9 : 0.5 : 1.0 : 1.2 : 6.0, PU grouting material has higher injectability and ideal compressive strength, which has been proved in grouting experiments.